Management of Melanaphis sorghi (Hemiptera: Aphididae) in grain sorghum with early planting and in-furrow flupyradifurone application. (February 2023) - Uyi, Osariyekemwen; Ni, Xinzhi; Buntin, David; Jacobson, Alana; Reay-Jones, Francis P.F.; Punnuri, Somashekhar; Toews, Michael D.
Abstract: Melanaphis sorghi is a key pest of sorghum production across the southern USA, where it causes serious damage that can lead to 100% grain yield loss in severe situations. Studies aiming to refine IPM strategies are crucial to improve management of this invasive pest. Here, the authors investigated the impact of planting date and insecticide application methods, including in-furrow vs. foliar applications, on M. sorghi infestation and grain sorghum yield. Field trials with four insecticide treatments (untreated, flupyradifurone in-furrow at 117 g/ha, flupyradifurone in-furrow at 146 g/ha, and flupyradifurone foliar at 73 g/ha) and two planting dates (mid-April to early May = early planting and late May to early June = late planting) were conducted on grain sorghum at Tifton, Georgia and Florence, South Carolina, in 2020 and 2021. Generally, early planted sorghum supported higher aphid density and severity of infestation as evident in the greater cumulative insect days in early planted sorghum in both Florence and Tifton. While a single foliar insecticide application immediately reduced infestations below the economic threshold, the lower rate in-furrow insecticide application significantly suppressed aphid density to near zero levels. These results suggest that foliar insecticide applications suppressed aphid densities, but were less consistent compared to in-furrow applications. Early planting dates and in-furrow insecticide treatments resulted in highest grain yield in both study locations. These data strongly suggest that planting early and using an in-furrow insecticide is the most consistent way to suppress M. sorghi infestations and improve grain yield in sorghum production in southern USA. Highlights: Early planted sorghum supported higher Melanaphis sorghi infestation. A single foliar insecticide application significantly reduced aphid infestation. In-furrow insecticide application suppressed aphid density to near zero levels. Early planting dates and in-furrow insecticide treatments improved grain yield.